An Attachment-Based Parental Capacity Assessment to Orient Decision-Making in Child Protection Cases: A Randomized Control Trial. (February 2022) - Cyr, Chantal; Dubois-Comtois, Karine; Paquette, Daniel; Lopez, Leonor; Bigras, Marc
Two parenting capacity assessment (PCA) protocols, with a short parent-child intervention embedded in each protocol, evaluated the potential for enhanced parenting to orient child placement decision. Parents ( n = 69), with substantiated reports of maltreatment by child protective services, and their children (0–6) were randomly assigned to one of two PCAs with either the Attachment Video-feedback (PCA-AVI) or a psychoeducational intervention (PCA-PI) as the embedded intervention component. The PCA-AVI group showed the highest increases in parent-child interaction quality at post-test. Also, at PCA completion, evaluators' conclusions about the parents' capacity to care for both PCA groups were associated with parent-child interactive improvements at post-test, the court's placement decision at post-test, and child placement one year later. However, only conclusions drawn by PCA-AVI evaluators were predictive of child re-reports of maltreatment in the year following PCA. PCAs, relying on short attachment interventions to assess the potential for enhanced parenting, are promising tools to orient child placement decisions.